Hiding the Word: Examining the Relationship Between a New Measure of Religiosity and Sexual Behavior - Young, Michael Dunlop (Journal of religion and health, 2015)
The relationship between religiosity and sexual behavior has been previously investigated, but researchers have not examined the relationship between the intellectual dimension of religiosity and sexual behavior. In this study, we developed an intellectual measure of religiosity, Hiding the Word (HTW), and examined whether it accounted for variation in the sexual behavior of college students, beyond that for which age and a generic measure of religiosity could account. Results showed, after accounting for age and generic religiosity, HTW made a significant contribution to distinguishing between students who had, and those who had not, engaged in various sexual behaviors. For females, this was the case in three of the five behaviors examined (all except receiving oral sex and participating in unprotected penile-vaginal intercourse at most recent sexual encounter), and for males, two of the four behaviors (sexual intercourse and anal intercourse). HTW was less of a factor in accounting for variation in the frequency of participation. For males, HTW was significant for the frequency of participation in penile-vaginal intercourse, receiving oral sex, and the number of sexual partners in the last month. For females, HTW was significant only for the number of sexual partners in the last month. Thus, religiosity, and specifically HTW, seems to play more of a role in determining whether or not a person has participated in behavior, rather than in the frequency of participation.